Microdissected Pyramidal Cell Proteomics of Alzheimer Brain Reveals Alterations in Creatine Kinase B-Type, 14-3-3-γ, and Heat Shock Cognate 71 - Sandebring-Matton, Anna; Axenhus, Michael; Bogdanovic, Nenad; Winblad, Bengt; Schedin-Weiss, Sophia; Nilsson, Per; Tjernberg, Lars O. (Frontiers in Aging Neuroscience, 2021)
Novel insights on proteins involved in Alzheimer disease (AD) are needed. Since multiple cell types and matrix components are altered in AD, bulk analysis of brain tissue may be difficult to interpret. In the current study, we isolated pyramidal cells from the CA1 region of the hippocampus from five AD and five neurologically healthy donors using laser capture microdissection. The samples were analysed by proteomics using 18O labeled internal standard and nano-HPLC MS/MS for relative quantification. Fold change between AD and control was calculated for the proteins that were identified in at least two individual proteomes from each group. From the ten cases analyzed, sixty-two proteins were identified in at least two AD cases and two control cases. Creatine Kinase B-type (CKB), 14-3-3-γ and Heat Shock Cognate 71 (Hsc71) which have not been extensively studied in the context of human AD brain previously, were selected for further studies by immunohistochemistry (IHC). In hippocampus, semi-quantitative measures of IHC staining of the three proteins confirmed the findings from our proteomic analysis. Studies of the same proteins in frontal cortex revealed that the alterations remained for CKB and 14-3-3-γ but not for Hsc71. Protein upregulation in CA1 neurons of final stage AD is either a result from detrimental, pathological effects, or from cell specific protective response mechanisms in surviving neurons. Based on previous findings from experimental studies, CKB and Hsc71 likely exhibit protective effects, whereas 14-3-3-γ may represent a detrimental pathway. These new players could reflect pathways of importance for development of new therapeutic strategies.